2003
DOI: 10.1109/jsen.2003.820363
|View full text |Cite
|
Sign up to set email alerts
|

A novel NO/sub 2/ gas sensor based on bis[phthalocyaninato] samarium complex/silicon hybrid charge-flow transistor

Abstract: A new kind of sandwich-like bis[2,3,9,10,16,17,23,24-octakis(octyloxy)phthalocyaninato] samarium complex Sm[Pc ] 2 (Pc = Pc(OC 8 H 17 ) 8 ) is used as film-forming material. Pure Sm[Pc ] 2 and mixture of Sm[Pc ] 2 and octadecanol(OA) deposited from both pure water and 10 4 M Cd 2+ subphases are investigated. It is found that a mixture of 1:3 Sm[Pc ] 2 :OA forms an excellent material for the fabrication of the gas-sensing Langmuir-Blodgett (LB) film by studying the film-forming characteristics. A new gas sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Cross-sectional view of the CMOS-MEMS gap-closing capacitive sensors with in-plane and out-of-plane sensing electrodes. [1][2][3]5]. These dry-etching processes can provide clean and directional structure geometry.…”
Section: In-plane Gapmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional view of the CMOS-MEMS gap-closing capacitive sensors with in-plane and out-of-plane sensing electrodes. [1][2][3]5]. These dry-etching processes can provide clean and directional structure geometry.…”
Section: In-plane Gapmentioning
confidence: 99%
“…CMOS-MEMS capacitive sensors have been widely used to detect the changes of various physical quantities such as acceleration [1][2][3], humidity [4], angular rate [5], etc. Presently, many studies are being reported to improve the performance of capacitive-type CMOS-MEMS sensors.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the increasing demand for microdevices with high sensitivity and high performance, bulk micromachining has been developed to create microstructures with thick layers similar to those achieved by the bulk silicon-dissolved wafer process, based on the self-stopped etch technique of heavy boron-doped silicon [6]. This fabrication technology is widely used to make microaccelerometers [7,8], microgyroscopes [9,10], microswitches [11,12], and microgears [13]. This technology also exhibits curvature behavior because its boron-doping mechanism is the same as that used in surface micromachining [5].…”
Section: Introductionmentioning
confidence: 99%
“…UV-visible spectra of thin films of bisphthalocyanines are susceptible to the exposure of electron donor and electron acceptor gases. Langmuir-Blodgett films of erbium bis[octakis(octyloxy)phthalocyaninato] complex were exploited for use in different types of room temperature conductometric NO 2 sensors (Xie et al 2001(Xie et al , 2003. The exposure of LuPc 2 to NO x caused the shift of the Q-band to a higher wavelength, leading a change in the film colour from green to red.…”
Section: Introductionmentioning
confidence: 99%